An LCMS method for the assay of melittin in cosmetic formulations containing bee venom - Tusiimire, Jonans; Wallace, Jennifer; Dufton, Mark; Parkinson, John; Clements, Carol J.; Young, Louise; Park, Jin Kyu; Jeon, Jong Woon; Watson, David G. (Analytical and Bioanalytical Chemistry, 2015)
There is a growing interest in the potential of bee venom in cosmetics as a rejuvenating agent. Products currently on the market do not specify exactly their content of bee venom (BV). Therefore, we developed a method for the detection and quantification of melittin, as a marker of bee venom content, in selected commercial creams which contained BVaccording to their marketing claims, in order to gauge the relative quality of such formulations. A quantitative method was achieved following a rigorous extraction procedure involving sonication, liquid-liquid extraction and solid phase extraction since carryover of excipients was found to cause a rapid deterioration in the chromatographic performance. The method employed a standard additions approach using, as spiking standard, purified melittin isolated from bee venom and standardised by quantitative NMR. The aqueous extracts of the spiked creams were analysed by reversed phase LCMS on an LTQ Orbitrap mass spectrometer. The purity of the melittin spiking standard was determined to be 96.0 %. The lowest measured mean melittin content in the creams was 3.19 ppm (±1.58 ppm 95 % CI) while the highest was 37.21 ppm (±2.01 ppm 95 % CI). The method showed adequate linearity (R2≥0.98) and a recovery of 87.7–102.2 % from a spiked blank cream. An assay precision of <20 % RSD was achieved for all but one sample where the RSD value was 27.5 %. The method was sensitive enough for use in routine assay of BV-containing cosmetic creams. Differences in the melittin content of the commercial products assayed were nearly tenfold.
Keywords: Bee venom; Extraction; LCMS; Creams; Cosmetics; Quantitative NMR